2018
DOI: 10.1108/ijmhsc-12-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

Health and well-being of Nepalese migrant workers abroad

Abstract: Purpose-Although South Asia is a growing supplier of migrant labour, there is a paucity of research on the health and wellbeing of male Nepalese migrant workers. This study assessed the health and mental wellbeing of Nepalese construction and factory workers employed in Malaysia, Qatar, and Saudi Arabia. Design-A structured questionnaire administered, in and around Nepal's international airport, to 403 migrants who had worked for over six months in their host countries. Logistic regression was used to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Another socio-demographic variable associated with quality of life and mental health symptoms is self-rated physical health (Al-Maskari et al , 2011;Nadim et al , 2016). Most participants in this study rated their health as good or very good, whereas migrant workers who rated their health as fair or poor reported increased mental health problems (Britto et al, 2016;Adhikary et al, 2018;Kumparatana et al, 2017). The findings indicated that participants who rated their physical health as poor were more likely to have mental health symptoms.…”
Section: Discussionmentioning
confidence: 72%
“…Another socio-demographic variable associated with quality of life and mental health symptoms is self-rated physical health (Al-Maskari et al , 2011;Nadim et al , 2016). Most participants in this study rated their health as good or very good, whereas migrant workers who rated their health as fair or poor reported increased mental health problems (Britto et al, 2016;Adhikary et al, 2018;Kumparatana et al, 2017). The findings indicated that participants who rated their physical health as poor were more likely to have mental health symptoms.…”
Section: Discussionmentioning
confidence: 72%
“…Like this study, a previously conducted exploratory study of Nepali migrants working in the Middle East and Malaysia highlighted that healthcare access depends on company size and the generosity of employers [ 16 , 17 ]. Lee and colleagues [ 18 ] and Joshi et al [ 19 ] also confirm the finding of our study: Indian, Bangladeshi and Myanmar migrants in Singapore and Nepali migrants in the Gulf countries had similar challenges to accessing health services as they lacked health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…However, this income is often generated at a great personal cost to the workers. The literature highlights several health issues of migrants in GCC and Malaysia, such as accidents and injuries due to poor health and safety at work [3][4][5]. The Foreign Employment Board (FEB) of Nepal reports around 1000 deaths of Nepali migrant workers in the GCC and Malaysia every year and of these around 1 in 10 deaths in males and 1 in 3 deaths in females are due to suicide [1].…”
Section: Introductionmentioning
confidence: 99%